2015
DOI: 10.1111/odi.12331
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle and dental attendance as predictors of oral health‐related quality of life

Abstract: Better health-related behaviors and routine dental attendance have a protective effect on OHRQoL. Clinicians should assess these behaviors during routine diagnostic workups. Global health authorities need to integrate oral and general health care and improve both OHrQoL and HrQoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
4
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 48 publications
4
51
4
1
Order By: Relevance
“…(). Routine dental attendance was reported to have a protective effect on oral health‐related quality of life in other studies (Almoznino et al., ).…”
Section: Discussionmentioning
confidence: 80%
“…(). Routine dental attendance was reported to have a protective effect on oral health‐related quality of life in other studies (Almoznino et al., ).…”
Section: Discussionmentioning
confidence: 80%
“…Vista la necesidad de mejorar la calidad de vida reduciendo el número de caries, proponemos lo que previamente en otras investigaciones se ha inferido: aumentar el número de visitas al dentista (36), impulsar los hábitos de higiene oral (37) o incluso, a través de la asistencia domiciliaria a las gestantes, potenciar su dedicación en salud oral (38).…”
Section: Discussionunclassified
“…1,2 It has been found that regular dental visits in children can result in positive oral health outcomes in adulthood. 3 The prevalence of untreated caries in at least 1 permanent molar was 20% in children aged 12-19 years.…”
mentioning
confidence: 99%